2014
DOI: 10.4103/0019-5413.132523
|View full text |Cite
|
Sign up to set email alerts
|

Isolated volar surgical approach for the treatment of perilunate and lunate dislocations

Abstract: Background:Volar and/or dorsal surgical approaches are used for surgical treatment of perilunate and lunate dislocations. There are no accepted approaches for treatment in the literature. We evaluated the functional results of isolated volar surgical approach for the treatment of perilunate and lunate dislocation injuries.Materials and Methods:9 patients (6 male and 3 female patients average age 34.5 ± 3.6 years) diagnosed with perilunate or lunate dislocations between January 2000 and January 2009 were involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Volar perilunate dislocations may frequently be associated with median nerve compression for which carpal tunnel decompression using the volar approach is required [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volar perilunate dislocations may frequently be associated with median nerve compression for which carpal tunnel decompression using the volar approach is required [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated comparable outcomes. Thus, the choice of approach is largely influenced by surgeon preference[ 10 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the palmar ligaments in the scaphoid proximal pole are theoretically important stabilizers, it is difficult to repair them by direct observation 7 . There are also publications showing that possible carpal tunnel syndrome can be treated in the same session by using the volar approach 8 . The reason why we prefer the dorsal approach in our practice is to have the chance to directly observe the scapholunate interval in addition to reduction with the dorsal approach and subsequent pin placement with direct observation.…”
Section: Discussionmentioning
confidence: 99%